THE URGENCY OF THE FINANCIAL SERVICES AUTHORITY’S ROLE IN ENSURING LEGAL CERTAINTY FOR DIGITAL FINANCIAL TRANSACTIONS IN THE MODERN ECONOMIC ERA - Putra, Dika Anggara (Yayasan Amanah Nur Aman, 2025)
The development of digital technology has had a significant impact on both global and national financial systems. The emergence of technology-based financial service institutions (financial technology or fintech) such as peer-to-peer lending, digital banking, and electronic payment systems has accelerated financial inclusion among the public. However, this phenomenon has also introduced new legal risks, including the misuse of personal data, illegal lending practices, and weak consumer protection. As an independent institution, the Financial Services Authority (Otoritas Jasa Keuangan/OJK) has an urgent need to strengthen its supervisory and regulatory roles in the digital financial sector to ensure that it operates in a fair, transparent, and accountable manner. This research employs a normative legal method with statutory (statute approach) and conceptual (conceptual approach) perspectives. The findings indicate that the OJK holds a high degree of urgency in responding to the digital transformation of the financial sector. Strengthening technology-based regulations, fostering inter-agency synergy (OJK–Bank Indonesia–Ministry of Communication and Information Technology), and enhancing digital financial literacy constitute the main pillars that must be reinforced to maintain the stability and fairness of the national financial system.